Consistent Systems of Finite Dimensional Distributions - Arzumanian, Victor; Nahapetian, Boris (Armenian Journal of Mathematics, 2015)
In the paper we discuss the problem of description of random fields by means of systems of finite dimensional probability distributions. We present from a unified point of view a survey of the various such systems associated with random fields. Then general system of finite dimensional distributions with a suitable consistency condition is introduced. The properties, relations with other systems, as well as the problems of existence and uniqueness of the corresponding random fields are discussed.